Biotechnology Advancements in Pediatric Health: Current Trends and Future Directions - Syafiq Irfan; Amir Hakimi Syah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Biotechnology is rapidly transforming pediatric healthcare by providing new treatments, diagnostic tools, and therapies for children. This paper reviews recent advancements in pediatric biotechnology, including gene therapy, immunotherapy, and personalized medicine. It explores the potential benefits of these innovations for treating genetic disorders, childhood cancers, and rare diseases, as well as the ethical considerations surrounding their use.